The Post-Pandemic Evolution of Telemedicine: Integrating AI for a New Era of Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The COVID-19 pandemic served as an unprecedented catalyst, fundamentally reshaping the landscape of healthcare delivery. Overnight, telemedicine transitioned...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics